Review on Green and Efficient Synthesis of Schiff Bases and Transition Metal Complexes (International Journal of Scientific Research in Science and Technology, 2024)
These reviews focus on synthesizing Schiff bases and transition metal complexes using a microwave-assisted method. This method is rapid, efficient, clean and ecologically caring. The special method provides several advantages: environmental friendliness, simple work-up procedure, short reaction times, non-hazardous and excellent yields. The microwave-assisted method has become a new and rapidly growing area in man-made organic chemistry. In many cases, reactions that normally require many hours at reflux temperature under classical conditions can be completed in a microwave oven within several minutes or even seconds. Recent simplifications of microwave reaction enhancement techniques have increased microwave ovens’ safety and practical utility for their use in chemical laboratories without any modification. The biological activity data show that some metal complexes are more effective than the free ligand. These compounds show different biological activities, including antifungal, antibacterial, antitubercular, antiviral, antimalarial, antidiabetic, anticancer, antioxidant, antidiuretic, anti-inflammatory, and antipyretic. This review discusses the synthesis and biological applications of Schiff bases synthesized using microwave irradiation.